The Economic Space in the Region: The Theoretical Approaches to the Study - Litvinenko, Inna L.; Kaminskaya, Anastasiya S.; Prokhorova, Victoria V.; Belova, Elena O.; Shutilov, Fedor V.; Sheludko, Elena B. (International Review of Management and Marketing, 2016)
Modern Russia as a federal state is inseparably linked with the overcoming of spatial disparities and economic development, regional features in achieving common strategic objectives; spatial disparities and economic development of its regions due to the presence or absence of mineral resources, highly qualified human capital, and the density of the industrial complex and other factors. Uneven spatial and economic development of regions of the Russian Federation could contribute to the growth of social tension, acceleration of migration flows and lead to unpredictable social and economic consequences. The main job of the regional economy is an objective assessment of the spatial and economic development of Russian regions, the identification of the causes of the backlog in the formation and development of some of them, as well as the development of theoretical approaches, methods and techniques of regional development and the use of their material conditions. Keywords: Regional economy, economic space, industrial complex JEL Classifications: L16; P25; R11